An Epidemiological Study to Find out Risk Factors of Multi Drugs Resistance Tuberculosis in Nepal (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2018)
Introduction: Drug resistant tuberculosis is a threat to tuberculosis control worldwide. Previous anti- tuberculosis treatment is a widely reported risk factor for multi drug resistant tuberculosis (MDR-TB), whereas other risk factors are less well described. In Nepal National Tuberculosis Control Programme initiated DOTSPLUS Pilot project from September 2005 using standardized treatment regimen.Objective: To explore the risk factors for MDR-TB in Nepal.Methodology: Institution based matched case control study with a case: control ratio of 1:2 was carried out in three regions of Nepal. Fifty five cases and 110 controls were selected. Current MDR-TB patients on treatment from DOTS–Plus clinic were enrolled as cases. Controls were age, sex matched cured TB patients and who had completed treatment either from the same centre or any DOTS Centre adjacent to that DOTS Plus Centre. Data was collected by a trained research assistant using interviewer administered structured questionnaire. Matched analysis was done using SPSS 16 version. Confounding effects were controlled by using matching, matched analysis and regression analysis.Results: In matched analysis following were the significant risk factors for MDR-TB in Nepal.(1) HIV Sero positivity (OR 15.9, CI 1.9- 133.0) (2) Travel cost more than 50 NRs per day (OR 6.5, CI 2.4- 9.8) (3) Contact history of TB (OR 3.8, CI 2.2- 6.6) (4) Living in a nuclear family (OR 6.0, CI 2.6- 13.9)(5) Non adherence to DOTS (OR 18.6, CI 2.27- 151.0) (6) Distance to treatment centre more than 5 Km ( OR 3.9, CI 1.5- 10.) (7) Previous history of TB ( OR 12.0, CI 5.4 -26.5)(8) Living in a rural area (OR 4, CI 2.1- 8.5) (9) Unmarried (Crude OR 3.3,CI 1.6- 6.8) (10) Un-employment (OR 3.4,CI 1.6-7.6)(11) Living in a rented house (OR 3.5, CI 1.77- 3.67) (12) Single bed room (OR 2.8, CI 1.13- 6.9).  Using muti-variate analysis except living in a rented house and single bed room other variables were positive significant predictors for MDR –TB in Nepal.Conclusions: Many risk factors were related to the DOTS. Strengthening of DOTS programme to tackle the identified risk factors can reduce the MDR –TB burden in Nepal.SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, Vol. 14, No. 2, 2017, Page: 31-38